Peningkatan Keterampilan Membaca Bacaan Berhuruf Jawa Melalui Model Pembelajaran Talking Stick Teknik Permainan Butakali (Piwulang : Jurnal Pendidikan Bahasa Jawa, 2022)
The low learning outcomes of reading Javanese letters in class VIII H SMP Negeri 1 Kesesi for the even semester 2021/2022 school year requires teachers to find ways to arouse students' feelings of pleasure towards the learning. This study aims to determine the magnitude of the increase in reading skills in Javanese letters and to describe changes in student learning behavior after using the Talking Stick learning model with the Butakali game technique (Word and Sentence Hunt). This research is qualitative research with two cycles using test and non-test data collection techniques. The test technique is used to obtain the value of learning outcomes. The non-test technique was carried out to obtain student data. The process of data analysis is carried out during the implementation of learning on the data that has been collected. The results showed an increase in reading skills in Javanese letters and changes in students' learning behavior. The average score achieved by students in reading Javanese letters in the initial conditions the average achieved was 65.44, increasing to 73.38 in the first cycle, and increased to 81.03 in the second cycle. In terms of changes in learning behavior, it is in the form of an increase in positive behavior and a significant decrease in negative behavior after using the Talking Stick learning model of the Butakali game technique (Word and Sentence Hunt) in learning to read Javanese letters.